Cytokines and Abnormal Glucose and Lipid Metabolism - Shi, Jie; Fan, Jiangao; Su, Qing; Yang, Zhen (Frontiers in endocrinology (Lausanne), 2019)
Clear evidence indicates that cytokines, for instance, adipokines, hepatokines, inflammatory cytokines, myokines, and osteokines, contribute substantially to the development of abnormal glucose and lipid metabolism. Some cytokines play a positive role in metabolism action, while others have a negative metabolic role linking to the induction of metabolic dysfunction. The mechanisms involved are not fully understood, but are associated with lipid accumulation in organs and tissues, especially in the adipose and liver tissue, changes in energy metabolism, and inflammatory signals derived from various cell types, including immune cells. In this review, we describe the roles of certain cytokines in the regulation of metabolism and inter-organ signaling in regard to the pathophysiological aspects. Given the disease-related changes in circulating levels of relevant cytokines, these factors may serve as biomarkers for the early detection of metabolic disorders. Moreover, based on preclinical studies, certain cytokines that can induce improvements in glucose and lipid metabolism and immune response may emerge as novel targets of broader and more efficacious treatments and prevention of metabolic disease.